Integrating Tasawwuf to Psychotherapy: A Comparative Study of Nursamad Kamba and Abdallah Rothman - Amal, Arifa; Othman, Siti Suriani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The integration of psychotherapy with tasawwuf has become prominent topic in the field of psychology over the past few decades, largely due to the perception that modern psychology has failed to provide solutions for the increasing mental health problems. Classical tasawwuf and Islamic scholarly traditions are now being paid attention as both are considered to offer effective alternatives. This article aims to explore the expansion of tasawwuf discourse from the realm of spiritual-religious experience into an intellectual-discursive dimension. The study focuses on the efforts of two prominent figures, Nursamad Kamba and Abdalla Rothman, in integrating Islamic tasawwuf and conception of soul with modern psychotherapy. Research was conducted through interview and literature review using content analysis methods. The results indicate that the common ground between the two lies in their awareness of the fundamental relevance of Islamic concepts to modern psychology and psychotherapy. However, there are substantial differences between them that can be examined from ontological, epistemological, methodological, and practical aspects. Nursamad Kamba comprehensively integrates the entirety of tasawwuf with psychotherapy, which had been established as a university study program. Whereas Abdallah Rothman formulated his conception as a theoretical model of Islamic Psychotherapy applicable in clinical practice. Theoretically, this study has implications for strengthening the philosophical discourse on the integration of Islamic scholarly tradition of tasawwuf and psychotherapy and encourages cross-cultural and interdisciplinary research. Practically, it promotes collaboration between academics and practitioners trained in both Islamic and Western psychotherapy traditions to address complex mental health issues and improve the overall mental well-being of society.